Weed–crop competition under improved nutrient management reveals trade-off between yields and weed diversity in organic farming - Karlsson, Melanie ; 0000-0002-2865-2284; Carrié, Romain; Wetterlind, Johanna; Bergkvist, Göran; Ekroos, Johan; Smith, Henrik G. ; 0000-0002-2289-889X (Biological Agriculture and Horticulture, 2025)
In the pursuit of more sustainable agriculture, weeds play a dual role by threatening crop production and simultaneously contributing to farmland biodiversity. Management actions such as the use of fertilisers (fertilisation) may change weed abundance and community composition with consequences for both weed–crop competition and biodiversity. Alleviating the balance between yield and biodiversity requires a mechanistic understanding of how fertilisation impacts weed diversity and functional community composition. To investigate this, an experiment was conducted in an organic spring wheat field in Sweden, using a split-plot randomised complete block design with crossed fertilisation and weeding treatments. The experimental design took advantage of existing variation in soil conditions, resulting in different concentrations of available nitrogen in the soil supply. With increased fertilisation and soil nitrogen supply, crop yield increased, whereas weed evenness decreased. Additionally, average weed seed mass, specific leaf area and nectar production of the weed community decreased with higher soil nitrogen supply, whilst the relevance of the weed communities for biodiversity increased. Importantly, the results showed that weed-induced yield loss depended on the fertilisation rate and soil nitrogen supply. This suggested that development of sustainable weed management should not only focus on minimising weed abundance but also on identifying nutrient management regimes that minimise the trade-offs between yield, competition, and biodiversity.
Keywords: Chessboard experiment; fertilisation; organic agriculture; soil nitrogen; spring wheat; weed community